A PRME response to the challenge of fighting poverty: How far have we come? Where do we need to go now?. Issue 2 (July 2017) - Rosenbloom, Al; Gudić, Milenko; Parkes, Carole; Kronbach, Britta
Abstract: The Sustainable Development Goals (SDGs) encompass the most difficult and complex challenges facing the world today. Heading up the goals, in common with the Millennium Development Goals (MDGS), is the eradication of poverty 'in all forms everywhere'. This requires strategies, innovations and actions from all sectors in society and not least from business and education. With the forthcoming 10th Anniversary of PRME, this paper examines the role of the PRME Working Group, established in 2008, on Poverty, a Challenge to Management Education (referred to as the Anti-Poverty WG) in integrating poverty into management education at all levels worldwide. As a context for the Anti-Poverty WG, the evolving thinking and approaches to the business role in poverty alleviation are examined. The key areas of the group's work over the last decade are then discussed. This includes the research undertaken to understand the issues and challenges of integrating poverty into management education, the subsequent publications in the form of reports, books and articles and the engagement of the business community and management educators through conferences and other outreach events and activities. Finally, this paper explores the current SDG agenda to reflect on the challenges that still lie ahead. Highlights: Summary of the business literature on poverty. Achievements of PRME Anti-Poverty Working Group. Challenges of integrating poverty into business and management courses.